Market institutions transformation in modern Russian economy - Krasilnikov, Oleg Yurievich (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. The article discusses the problems of market institutions transformation in modern Russian economy. Transformation is understood primarily as the degradation of the economic institutions’market nature. There is a tendency towards their increasing nationalization and centralization. Theoretical analysis. The degradation of market institutions is expressed, first of all, in the transformation of the property institution, which is drifting towards increasing nationalization. In recent years, there has been a clear trend towards the nationalization of private companies, which occurs for various reasons, ranging from the return of defense and systemically important enterprises to state ownership and ending with the presence of a criminal trail and extremist activities. There is also an increase in government regulation of commodity and monetary circulation, institutions of payment and settlement and banking systems, and pricing. The burden of taxation is increasing, as well as fines. In addition, a card system for the distribution of food products for mass consumption is being introduced in some regions. Opinions are expressed on the need to introduce the Institute of economic planning. Results. A conclusion is drawn that, from the point of view of institutional theory, modern Russian economy increasingly resembles a system inherent not in a contractual, but in an exploitative model of the state. The main indicators of this system are high military and administrative costs, nationalization of private property, increased taxes and fines, and a decrease in real incomes of the population.